The use of suplementary materials in ESL clases: a comparative analysis of public and private high schools. - Freire Castro, Cecilia Verónica (2012)
This research was focused on the use of supplementary materials in ESL classes: a comparative analysis of public and private high schools which aims are to determine and analyze the type of supporting materials used in ESL public and private high schools, as well as to compare the supporting materials used in private and public high schools. This study was done in New York in the boroughs of the Bronx and Manhattan where the participants were the ESL teachers and the students from the ESOL level 1, 2 and 3 whose ages ranged between 15 to 18 years old. Furthermore, qualitative and quantitative were the methods used for this investigation; the first one describes the aspects regarding pertinence, appropriateness and quality of each supplementary material used by the teacher, and the second one analyzes and compares the frequency and variety used in the classroom. This investigation has demonstrated that the use of the visual materials prevailed over other teaching methods, especially the whiteboard which is the most frequently tool used by the teachers in their classes in both high schools.